A Path Beyond Metal and Silicon:Polymer/Nanomaterial Composites for Stretchable Strain Sensors. (18th February 2019) - Qiu, Aidong; Li, Peilin; Yang, Zhaokun; Yao, Yu; Lee, Ivan; Ma, Jun
Abstract: Conventional strain sensors based on metals and semiconductors are rigid and cannot measure soft and stretchable objects. Thus, new strain sensors based on polymer/nanomaterial composites are attracting more interest. Although much effort has been dedicated to achieve high values of both sensitivity and stretchability with linearity, this work endeavors to search and establish guidelines for the development of stretchable strain sensors, by critically reviewing conventional sensors and examining recent progress. It starts from introducing key parameters for conventional strain sensors; these parameters are further discussed for their potential impact on new polymer/nanomaterial strain sensors. The work concludes that there are no general benchmarks for conventional strain sensors utilized in industry. From the findings, the authors suggest that stretchable strain sensors should be custom designed and developed to meet particular measurement requirements, in comparison with a generic aim of yielding a sensor with high degrees of stretchability, sensitivity, and linearity. Challenges are discussed, including reliability, calibration to be used as proper gauges, and soft data acquisition systems. Abstract : Stretchable strain sensors can fulfill the dream of measuring soft and stretchable objects, where conventional metal or semiconductor strain sensors are ineffective. Through reviewing conventional and recent strain sensors, this work suggests application‐focused strategies. Outlook and challenges are discussed, including reliability, calibration to be used as proper gauges, and soft data acquisition systems.